1979
DOI: 10.2307/2010082
|View full text |Cite
|
Sign up to set email alerts
|

Agenda Setting and Bargaining Power: The Mexican State Versus Transnational Automobile Corporations

Abstract: The authors explore the often conflictual bargaining relations between transnational corporations and host governments of less developed countries. They focus particular attention on the conflict that surrounded the creation of the Mexican automobile industry (1960–1964), criticizing and reformulating a current approach to these issues. The argument proceeds in two parts—agenda setting and bargaining power. Each part is organized around a central criticism of the bargaining power approach and provides an alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

1989
1989
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(5 citation statements)
references
References 18 publications
0
3
0
2
Order By: Relevance
“…A large number of these investigations have been case-specific rather than cross-national, and have concentrated on a particular industry or sector. Bennett and Sharpe (1979) found that the obsolescing model did not apply in the case of foreign investment in the Mexican automobile industry. The authors contend that high technology-intensive consumer goods manufacturing sectors like the automobile industry exhibit different characteristics from the extractive sector.…”
Section: Framing the Analysismentioning
confidence: 99%
“…A large number of these investigations have been case-specific rather than cross-national, and have concentrated on a particular industry or sector. Bennett and Sharpe (1979) found that the obsolescing model did not apply in the case of foreign investment in the Mexican automobile industry. The authors contend that high technology-intensive consumer goods manufacturing sectors like the automobile industry exhibit different characteristics from the extractive sector.…”
Section: Framing the Analysismentioning
confidence: 99%
“…In manufacturing and high‐tech industries, where local operations require lower investments or benefit from ongoing knowledge transfer from home operations, MNCs tend to maintain their bargaining power over time (Bennett and Sharpe, 1979; Grosse, 1996; Kobrin, 1987). Conversely, in industries characterized by asset specificity and high fixed costs – such as those based on exploitation of natural resources (Click and Weiner, 2010; Durnev et al, 2009), large infrastructure projects (Ramamurti and Doh, 2004) or the provision of essential services such as telecommunications, water, electricity and gas (García‐Canal and Guillén, 2008) – the MNC’s bargaining power tends to erode more rapidly, as it is more costly for it to leave the country (Kobrin, 1982; Maurer, 2013).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Z początkowych siedmiu producentów samochodowych do początku lat osiemdziesiątych XX wieku ich liczba zmalała do pięciu (Ford, GM, Chrysler, Volkswagen, Nissan). Spadek ten wynikał głównie z faktu, iż firmy z meksykańskim kapitałem nie sprostały konkurencji i zakończyły produkcję lub zostały przejęte przez międzynarodowe koncerny (Bennett, Sharpe, 1984;1985;Shapiro, 1993).…”
Section: Historia Rozwoju Meksykańskiego Przemysłu Motoryzacyjnegounclassified
“…Meksykański przemysł samochodowy zawdzięcza swoje powstanie inwestycjom bezpośrednim międzynarodowych koncernów samochodowych głównie z USA (GM, Ford, Chrysler), Europy Zachodniej (Volkswagen, Renault) oraz Japonii (Nissan) (Bennett, Sharpe, 1984;1985;Shapiro, 1993). Zmiana polityki poprzemysłowej Meksyku, w obliczu wyczerpywania się modelu industrializacji opartej na substytucji importu, wywołała kolejną falę napływu BIZ do tego sektora, związaną z budową nowych, zaawansowanych technologicznie fabryk silników oraz samochodów przeznaczonych głównie na eksport (Carrillo, 1991;Mortimore, 1995;Moreno-Brid, 1996).…”
Section: Nowa Fala Biz a Rozwój Meksykańskiego Przemysłu Samochodowegunclassified